Mechanical Behaviour of Inconel 718 Thin-Walled Laser Welded Components for Aircraft Engines - Enrico Lertora; Chiara Mandolfino; Carla Gambaro (International Journal of Aerospace Engineering)
Nickel alloys are very important in many aerospace applications, especially to manufacture gas turbines and aero engine components, where high strength and temperature resistance are necessary. These kinds of alloys have to be welded with high energy density processes, in order to preserve their high mechanical properties. In this work, CO2 laser overlap joints between Inconel 718 sheets of limited thickness in the absence of postweld heat treatment were made. The main application of this kind of joint is the manufacturing of a helicopter engine component. In particular the aim was to obtain a specific cross section geometry, necessary to overcome the mechanical stresses found in these working conditions without failure. Static and dynamic tests were performed to assess the welds and the parent material fatigue life behaviour. Furthermore, the life trend was identified. This research pointed out that a full joint shape control is possible by choosing proper welding parameters and that the laser beam process allows the maintenance of high tensile strength and ductility of Inconel 718 but caused many liquation microcracks in the heat affected zone (HAZ). In spite of these microcracks, the fatigue behaviour of the overlap welds complies with the technical specifications required by the application.